Influence of graded EDTA applications on mobilization and translocation of trace elements—a soil column experiment. Issue 2 (11th December 2017) - Bloem, Elke; Vogler, Iris
Abstract: Increasing concerns about potential environmental effects of ethylenediaminetetraacetic acid (EDTA) accumulation in soils require better understanding of its behavior and its effect on trace element mobilization. In this study we investigated the effect of EDTA on soil trace element mobilization in undisturbed soil columns taken from a heavy metal contaminated field. The columns were leached by EDTA solutions of different concentrations under unsaturated, steady‐state conditions. The transport of trace elements (Cd, Co, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Sn, Zn) and EDTA was monitored by regularly collecting the leachates. After the termination of the leaching experiment the soil columns were divided into 5 layers to determine trace elements and EDTA concentrations in the soil. The results revealed that the soil analysis alone was not suitable to infer mobilization or immobilization patterns in relation to the EDTA concentration, as the mobilized fraction was too small in relation to the total trace metal concentrations in the soil. Analysis of the leachates displayed that after 2–4 pore volumes the EDTA output concentration reached about 80% of the input concentration. The trace element concentrations in the leachates showed that some elements were mobilized by EDTA (Cd, Cu, Fe, Pb, Co, Ni, Zn) while others were immobilized (Mn, Cr, Mo, Sn) in the soil columns after EDTA application.